Study on Unloading Relaxation Characteristics of Columnar Jointed Rock Masses Based on Displacement Back Analysis - Yu, Jun; Zhang, Qiang; Xu, Weiya; Wang, Rubin; Zhang, Han (Frontiers in Earth Science, 2021)
In view of the issues about columnar joint rock relaxation in the process of diversion tunnel excavation of The Baihetan hydropower station. Based on the displacement monitoring data of the diversion tunnel excavation, this article deduced the deformation parameters of the excavated relaxed rock mass of columnar joint rock cavern. Relaxation factor is imported to describe the deterioration degree of anisotropic deformation parameters of relaxed columnar jointed rock mass. In this paper, the equivalent strain is proposed as the criterion of unloading relaxation and the equivalent strain threshold is given. Based on the excavation relaxation characteristics of columnar jointed rock mass, a program for calculating anisotropic elastoplastic model is developed. According to the model, the distribution of the relaxation zone after the diversion tunnel excavation is simulated, and compared with the results of the field acoustic detection, the correctness and rationality of the model is verified, which provides a necessary reference for the design and construction of hydropower projects.